Iconographic interpretation of the temple as a theological symbol in images of the Annunciation of the 14th and 15th centuries (Fenestella. Inside Medieval Art, 2020)
This article seeks to highlight the important symbolic Christian meanings hidden in some textual metaphors of the Old Testament, such as “templum Dei”, “house of Wisdom”, “aula regia”, “Sancta Sanctorum”, “tabernacle”, “altar”, “ark” and other similar expressions related to worship spaces. To make our approach clearer, we will proceed according to two complementary analyses: first of all, we will analyse some exegesis offered on these metaphorical terms by certain Fathers and theologians of the Eastern and Western Churches; second, we will analyse some pictorial images of the Annunciation of the 14th and 15th centuries that include a temple or chapel in the scene. From this double analysis, of texts and images, it will be possible to conclude that the temple painted in those images constitutes a visual metaphor that illustrates the Christological and Mariological meanings brought to light by the Fathers and theologians when interpreting the aforementioned Old Testament textual metaphors.
Keywords: Templum Dei; Virgin Mary; Annunciation; Christ's Incarnation; Divine maternity; Jacquemart de Hesdin; Melchior Broederlam; Master of Boucicaut; Brothers of Limbourg; Robert Campin; Jan van Eyck; Barthélemy d'Eyck; Jean Fouquet